Mechanical properties of clay masonry units: Destructive and ultrasonic testing. (20th September 2019) - Noor-E-Khuda, Sarkar; Albermani, Faris
Highlights: UPV tests conducted on old and new clay brick specimens. Compressive and flexural strength of clay bricks investigated. Correlations between UPV measurements from different directions presented. Correlations between UPV and compressive and flexural strength of clay bricks established. Flexural strength predicted by UPV was approx. 10% of the compressive strength. Abstract: The compressive and flexural strength of old and new clay bricks are investigated in this paper. Total 52 specimens comprising of old bricks collected from four different building sites in Western Australian and five different types of commonly used new bricks are used in the study. Ultrasonic pulse velocity (UPV) of the bricks were measured along the parallel and normal to the bed joint and parallel to the wall thickness directions. Compressive and flexural strength tests were conducted after the UPV testing. Results showed that the old bricks provided lower compressive strength which was well picked by the UPV readings. The flexural strength of the old bricks was comparatively higher than the new bricks. A common correlation between the compressive and flexural strength of the old and new bricks and the corresponding UPV readings is proposed, which can assist in on-site UPV testing of clay brick masonry buildings.